الحد من عمليات التسليم غير الضرورية في نظام بعيد المدى المتطور(LTE-Advanced) - الرضوان, هيثم; سعيد, محمد (Latakia University Journal -Engineering Sciences Series, 2018)
يعد تحسين أداء نظام بعيد المدى المتطور(LTE-Advanced) من حيث المردود وتقليل نسبة فقدان الحزم من المواضيع الهامة في مجال الاتصالات، حيث نستطيع تحقيق ذلك من خلال تحسين خوارزمية الاستلام والتسليم بين الخلايا في النظام وذلك عن طريق الحد من عمليات التسليم غير الضرورية مع الحفاظ على جودة الخدمة. ونظراً لعدم توفر الشبكة والمخدمات التي تعمل بنظام بعيد المدى المتطور على أرض الواقع؛ قمنا بمحاكاة الخوارزمية المقترحة على برنامج LTE-Sim)) والذي يؤمن محاكاة لعملية الاستلام والتسليم. حيث ضمت المحاكاة 7 خلايا سداسية وعدداً متغيراً من المستخدمين في كل محاكاة؛ وذلك لدراسة التحسينات الناتجة عن الخوارزمية المقترحة وتأثيرها على التأخير دون إهمال تغير عدد المستخدمين.قدم البحث طريقة لتحسين خوارزمية الاستلام والتسليم في نظام بعيد المدى المتطور عن طريق التركيز على مرحلة القياس وتحديد قيمة هامش الربح (HOM) بشكل ديناميكي حسب استخدام البيانات. باستخدام الخوارزمية المقترحة تظهر النتائج تحسيناً على المردود وتقليل نسبة فقدان الحزم، إلا أنه يوجد تأخير وذلك بسبب عملية التحقق التي تتم على نوع البيانات المستخدمة لدى المستخدمين. Improving the performance of Long Term Evolution-Advanced system (LTE-Advanced) in terms of throughput and minimize the lossless of the important topics in the field of telecommunications, where we can achieve this by improving the Handover algorithm between the cells in the system, by reducing the Handover of unnecessary operations while maintaining the quality of service optimally.Due to the lack of network servers that operate LTE-Advanced system provides on the ground; we have simulated the proposed algorithm on LTE-Sim software, which provides a simulation of Handover. Where simulation included seven hexagonal cells and a variable number of users in each simulation; and to study the resulting algorithm proposed improvements and their impact on the delay without neglecting change the number of users.Gave way to improve the Article algorithm receipt and Handover on a long-term system developed by focusing on the measurement phase, by determining the value of handover margin (HOM) dynamically Account to use the data. Using the proposed algorithm results show an improvement on the throughput and minimize the rate of lossless, but there is a delay Because the verification process carried out on the data used by the type of users.